Fibrin clot strength is associated with increased risk of major adverse cardiac events after TAVR - Hesselbarth, David; D’Orazio, Michelle; Ciccarone, Giovanni; Gjermeni, Diona; Jülch, Carina; Wessinger, Marius; Maslarska, Mariya; Rilinger, Jonathan; Hilgendorf, Ingo; Wolf, Dennis; Kaier, Klaus; Dürschmied, Daniel; et al. (Clinical research in cardiology, 2025)
Patients after transcatheter aortic valve replacement (TAVR) are at increased risk of both major adverse cardiac events (MACE), including ischemic and thrombotic complications, as well as significant bleeding. Given this delicate balance between prothrombotic and hemorrhagic risk, the assessment of hemostatic markers might help identify patients at increased risk.
Online veröffentlicht: 6. Oktober 2025
Gesehen am 04.12.2025